Effect of Teacher Competency, Motivation, and Welfare on Teacher Performance: Intervening of Teacher Certification - Arif Wahyu Wirawan; Hengky Pramusinto; Aan Ikhsananto (Economics Education Department Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of teacher competence, motivation, and welfare on teacher performance with teacher certification as an intervening variable. This study was conducted with teachers in the Teacher Professional Education Program in Economics Education at Semarang State University. This study used a quantitative, survey-based method, involving PPG teachers who had received certification. Data were collected through questionnaires and analyzed using path analysis to test the direct and indirect relationships between variables. The results showed that teacher competence had a positive and significant influence on teacher performance. Motivation also plays an important role in improving teacher performance, both intrinsic and extrinsic motivation. In addition, teacher welfare significantly influences performance, but this relationship is mediated by teacher certification. Teacher certification not only improves teacher welfare but also strengthens the influence of welfare on teacher performance. Competence, motivation, and welfare are important factors that influence teacher performance. Teacher certification acts as an intervening variable, strengthening the impact of welfare on performance. These findings underscore the importance of improving teachers’ competence, motivation, and well-being, as well as the need to expand access to certification to support better teacher performance.